2018
DOI: 10.1111/ijcp.13281
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient disposition in overcrowded hospitals: is it safe and effective to use reverse triage and readmission screening tools for appropriate discharge? An observational prospective study of an Italian II level hospital

Abstract: Summary Background Reverse triage (RT) identifies patients eligible for discharge and have been proposed to cope with daily surge. Nevertheless, early discharge could increase the rate of readmission. Our aim is to test the effectiveness and safety of RT alone and with readmission screening tools (Identification Senior At Risk [ISAR], HOSPITAL, and Groeningen Frailty Index [GFI] scores) to predict appropriate discharge. Material and methods We prospectively assessed every 4 days (t0) inpatients of medical divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, the SERAP could also be adopted in the practice of reverse triage, a strategy coping with unusually high-demand situations by identifying patients who no longer need in-hospital resources and is safe for early discharge. 48 , 49 , 50 The integration of high-quality readmission risk evaluation models into the decision-making algorithm for reverse triage has been shown to further improve patient safety by Caramello et al. 50 Further research needs to be conducted to validate the effectiveness and physician-perceived acceptability after incorporating the SERAP into the transitional care model and reverse triage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the SERAP could also be adopted in the practice of reverse triage, a strategy coping with unusually high-demand situations by identifying patients who no longer need in-hospital resources and is safe for early discharge. 48 , 49 , 50 The integration of high-quality readmission risk evaluation models into the decision-making algorithm for reverse triage has been shown to further improve patient safety by Caramello et al. 50 Further research needs to be conducted to validate the effectiveness and physician-perceived acceptability after incorporating the SERAP into the transitional care model and reverse triage.…”
Section: Discussionmentioning
confidence: 99%
“…48 , 49 , 50 The integration of high-quality readmission risk evaluation models into the decision-making algorithm for reverse triage has been shown to further improve patient safety by Caramello et al. 50 Further research needs to be conducted to validate the effectiveness and physician-perceived acceptability after incorporating the SERAP into the transitional care model and reverse triage.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 434 or 6% of patients had LOS for two nights, 369 or 5% for three nights, 3% or 226 for 4 nights and only 1% or 87 patients who stayed in the hospital for a long time (more than 4 nights). Many researchers took the limit of more than 4 nights as an indicator of prolonged hospitalization (Brandi et al, 2020;Caramello et al, 2019;Neto et al, 2020;Rezaianzadeh et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the existing severity triage lacks usefulness and causes disputes between patients and medical staff [11]. In overcrowded hospitals, the development of a safe discharge system to prioritize hospitalization will improve patient safety and reduce repeat visits [12]. It has also been reported that clinical evaluation is superior to the use of various severity triage systems [13].…”
Section: Discussionmentioning
confidence: 99%